Characterization of Rumen Microbiota of Two Sheep Breeds Supplemented With Direct-Fed Lactic Acid Bacteria - Mani, Sinalo; Aiyegoro, Olayinka A.; Adeleke, Matthew A. (Frontiers in Veterinary Science, 2021)
Supplementation of direct-fed microbials into ruminants' nutrition has shown great potential in manipulating rumen fermentation and enhancing productive animal performance. However, little is known about rumen microbial composition and diversity of Damara and Meatmaster sheep, breeds indigenous to South Africa. The study aimed to explore and compare the rumen microbiomes of two breeds at different feeding treatments as follows: no antibiotic, no probiotics (T1), only potential probiotic (T2), only potential probiotic (T3), combination of potential probiotics (T4), antibiotic (T5); using metagenomic approach. The results showed that based on Shannon index; microbial diversity of Damara was significantly higher than Meatmaster, while treatment T4 was significantly higher than treatment T1 (p < 0.05). Principal coordinate analysis showed no significant difference among treatments, while there were significant dissimilarities between sheep breeds and sample-day (p < 0.05). Canonical correspondence analysis (CCA) displayed the dispersion of microbial communities among treatments, where negative control (T1) was distinct from other treatments. Bacteroidetes and Firmicutes were the most abundant microbial phyla across treatments for both breeds. Negative control and the combination of potential probiotics showed lower proportions of Proteobacteria compared to other treatments. At the genus level, Prevotella and Clostridium were abundant across all treatments while Pseudomonas was abundant only in T2, T3 and T5. In all treatments, Fibrobacter was detected after the feeding trials, while it was not detected in most treatments before trials. The results revealed that the structure and abundance of rumen microbiome were altered by the administration of lactic acid as a putative probiotic.